Does Referral-Based Hiring Exacerbate Agency Problems? - Hung, Chung-Yu; Lillis, Anne M.; Wu, Anne (The Accounting Review, 2023)
ABSTRACT We investigate circumstances in which referral-based hiring can exacerbate rather than mitigate agency problems. When incentive contracts cannot fully align employees’ incentives with the interests of the firm, employees may behave opportunistically. Referred job candidates likely obtain inside information from existing employees about opportunistic incentive responses, and it is this information that exacerbates agency problems. Our research setting enables us to distinguish between referred and nonreferred employees. It also features a context in which the incentive contract consists of two measures with different properties (efficiency and quality), which allow for opportunistic incentive responses, i.e., sacrificing quality for efficiency. We find that referred employees focus more on efficiency and less on quality than nonreferred employees. We further document the persistence of this behavior and the differential departure likelihood of referred and nonreferred employees. Our findings suggest that referral-based hiring can exacerbate agency problems when incentive contracts allow for opportunistic gains. Data Availability: All data are proprietary. Confidentiality agreements prevent the authors from distributing the data.